In the era of targeted therapy and immunotherapy: advances in the treatment of large B-cell lymphoma of immune-privileged sites - Wang, Haotian; Zhang, Ying; Wan, Xin; Li, Zhaoxia; Bai, Ou (Frontiers in Immunology, 2025)
Primary large B-cell lymphomas of immune-privileged sites (IP-LBCLs) include primary central nervous system large B-cell lymphoma (PCNSL), primary vitreoretinal large B-cell lymphoma (PVRL), and primary testicular large B-cell lymphoma (PTL). These tumors not only have a unique anatomical distribution but also exhibit specific biological and clinical characteristics. Given the high biological overlap between intravascular large B-cell lymphoma (IVLBCL) and IP-LBCLs, and the fact that IVLBCL is confined to the intravascular microenvironment, IVLBCL is currently included in the category of IP-LBCLs. IP-LBCLs are associated with suboptimal prognosis. However, advancements in biomarker detection technologies have facilitated novel therapeutic approaches for this disease entity. This review aims to summarize and analyze the latest research progress in IP-LBCLs, with a focus on new treatment strategies in the era of targeted therapy and immunotherapy. It is intended to further understand the biological characteristics, treatment, and latest advancements of this disease.